Battle in the English Channel - Taylor, Theodore, 1921-2006.; Glass, Andrew, 1949- (New York, N.Y. : Avon Books, 1983)
Describes the events of the major sea battle in the English Channel in February 1942 when the British navy failed to capture several strate gically important German battleships.
Includes index.
Bibliography: p. 132-134.
Keywords: Scharnhorst (Battleship) -- Juvenile literature; Prinz Eugen (Cruiser) -- Juvenile literature; Gneisenau (Battleship) -- Juvenile literature; World War, 1939-1945 -- Campaigns -- English Channel -- Juvenile lit erature; Operation Cerberus, 1942 -- Juvenile literature; World War, 1939-1945 -- Naval operations, German -- Juvenile literat ure; Operation Cerberus, 1942.; World War, 1939-1945 -- Campaigns -- English Channel; World War, 1939-1945 -- Naval operations, German; English Channel -- History -- Juvenile literature; English Channel -- History